The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/ceat.201000570
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Carbonation and Sulfation of CaO in Oxy‐Fuel CFB Combustion

Abstract: For anthracites and petroleum cokes, the typical combustion temperature in a circulating fluidized bed (CFB) is > 900°C. At CO 2 concentrations of 80-85 % (typical of oxy-fuel CFBC conditions), limestone still calcines. When the ash which includes unreacted CaO cools to the calcination temperature, carbonation of fly ash deposited on cool surfaces may occur. At the same time, indirect and direct sulfation of limestone also will occur, possibly leading to more deposition. In this study, CaO was carbonated and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Wang et al investigated simultaneous carbonation and sulfation of CaO under oxyfuel CFBC conditions. 111 The results showed that, when the ash containing CaO cooled calcination temperature, carbonation of fly ash deposited on cool surfaces occurred. Simultaneously, indirect and direct sulfation of limestone would also occur, possibly leading to more deposition.…”
Section: Ash Formation and Deposition In Oxy-fbcmentioning
confidence: 98%
See 3 more Smart Citations
“…Wang et al investigated simultaneous carbonation and sulfation of CaO under oxyfuel CFBC conditions. 111 The results showed that, when the ash containing CaO cooled calcination temperature, carbonation of fly ash deposited on cool surfaces occurred. Simultaneously, indirect and direct sulfation of limestone would also occur, possibly leading to more deposition.…”
Section: Ash Formation and Deposition In Oxy-fbcmentioning
confidence: 98%
“…This was ascribed to the inhibition of sulfation by the high CO 2 partial pressure and the reduction of alkali metals in the fly ash. Wang et al also found that, under conditions of oxy-FBC, ash carbonation was faster than sulfation . The ashes generated in a 10 kW th fluidized bed unit using a Victorian brown coal in both air and oxyfuel combustion were characterized .…”
Section: Ash Formation and Deposition In Oxy-fbcmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcination is the first step, then followed by sulfation. The calcination reaction is faster than the sulfation reaction; meanwhile, CO 2 that is produced during calcination could form a Stefan flow that can make sulfation start to occur until the end of calcination, in principle. , In addition, both processes require much time and are greatly affected by the combustion process. , As a result, for a large amount of CaCO 3 and CaO particles, calcination and sulfation are not entirely separate processes: they are stored and recycled in the furnace under different conditions like coal particles. Therefore, the developments of soft sensing models for the desulfurization process have important practical significance.…”
Section: Introductionmentioning
confidence: 99%